Pendapatan dan Kelayakan Usahatani Tomat (Solanum lycopersicum L.) di Kecamatan Merdeka Kabupaten Karo - Siregar, Sasmita; Rangkuti, Khairunnisa; Panggabean, Syahib Ashiddiq (UNIVERSITAS LABUHANBATU, 2024)
This research aims to determine the level of income and feasibility of tomato farming in Merdeka District, Karo Regency. Determining the research location was carried out purposively. The number of sample farmers was 34 people using the Slovin method. The research results show that on average farmers manage 0.46 Ha of farming land. The largest component of production costs incurred by farmers in tomato farming in Merdeka District is pesticide costs amounting to IDR 13,302,852.92 or 31.76% of the total production costs. Meanwhile, the smallest cost component is the rope cost of IDR 600,000 or 1.43%. The average income of tomato farmers per planting season is IDR. 58,008,029.4 or Rp. 9,668,005 per month. Feasibility of farming with the R/C Ratio value per farmer in tomato farming is 2.385 and the B/C Ratio value is 1.385 which shows that the farming is economically feasible to operate. Keywords: farming, tomatoes, costs, income, feasibility